2017
DOI: 10.1016/j.contraception.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined oral contraceptives, depot medroxyprogesterone acetate and the levonorgestrel-releasing intrauterine system on the vaginal microbiome

Abstract: OBJECTIVES Prior studies suggest that the composition of the vaginal microbiome may positively or negatively affect susceptibility to sexually transmitted infections (STI) and bacterial vaginosis (BV). Some female hormonal contraceptive methods also appear to positively or negatively influence STI transmission and BV. Therefore changes in the vaginal microbiome that are associated with different contraceptive methods may explain, in part, effects on STI transmission and BV. STUDY DESIGN We performed a retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
114
1
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(119 citation statements)
references
References 41 publications
0
114
1
4
Order By: Relevance
“…Perhaps as a result of pre-IVF treatment with oral contraceptives and hormonal intrauterine device which have been reported to protect against BV bacteria. 29 BV was associated with a significantly higher early spontaneous abortion rate (RR 1.68, 95% I 1.24, 2.27; I 2 = 1%; Table 2), although this effect was not found to have a significant impact on other reproductive outcomes studied in this review. The quality of evidence was very low according to GRADE and more evidence, especially from interventionbased studies, is needed to draw firm conclusions regarding the cause and effect of abnormal vaginal microbiota and the reproductive outcome of IVF patients.…”
Section: Main Findingsmentioning
confidence: 71%
See 1 more Smart Citation
“…Perhaps as a result of pre-IVF treatment with oral contraceptives and hormonal intrauterine device which have been reported to protect against BV bacteria. 29 BV was associated with a significantly higher early spontaneous abortion rate (RR 1.68, 95% I 1.24, 2.27; I 2 = 1%; Table 2), although this effect was not found to have a significant impact on other reproductive outcomes studied in this review. The quality of evidence was very low according to GRADE and more evidence, especially from interventionbased studies, is needed to draw firm conclusions regarding the cause and effect of abnormal vaginal microbiota and the reproductive outcome of IVF patients.…”
Section: Main Findingsmentioning
confidence: 71%
“…In contrast, endometriosis was significantly less prevalent in IVF patients with BV than in patients with normal vaginal microbiota ( P = 0.02). Perhaps as a result of pre‐IVF treatment with oral contraceptives and hormonal intrauterine device which have been reported to protect against BV bacteria . BV was associated with a significantly higher early spontaneous abortion rate (RR 1.68, 95% I 1.24, 2.27; I 2 = 1%; Table ), although this effect was not found to have a significant impact on other reproductive outcomes studied in this review.…”
Section: Discussionmentioning
confidence: 84%
“…Several studies report the effect of hormonal contraceptives on the VMB (2, 5-10, 42-44). While some studies found subtle VMB shifts in women on hormonal contraceptives like enhanced Lactobacillus species (5, 8), reduced total bacteria (9), G. vaginalis (9), or lactobacilli (6), the majority do not show any major effects of hormonal contraceptives on VMB clustering (2, 7, 43) or associations between hormonal contraceptives and the proportion Lactobacillus -dominant VMB (42). Similarly, the taxa bar charts, PCoAs, heatmap, and cluster dendrogram in our study do not demonstrate any major effects of hormonal contraceptives on VMB clustering or associations between hormonal contraceptives and the proportion Lactobacillus -dominant VMB (except more borderline Lactobacillus -dominance in DMPA group), suggesting the effect of MPA on the VMB is more subtle than initially expected.…”
Section: Discussionmentioning
confidence: 99%
“…Another study analyzed the vaginal microbiome changes with different birth control methods, including LNG IUD, and found that LNG IUD users were more often colonized with BV-associated bacteria than were oral contraceptive users. 77 Of interest, a recent study showed no vaginal microbiome alteration 12 months after insertion of either a copper IUD or LNG IUD. Therefore, whether a change in the microbiome composition after insertion of an IUD affects EC risk is still not known.…”
Section: Intrauterine Devices Ec and The Microbiomementioning
confidence: 99%
“…prospectively investigated the microbiome change 1 week before and 12 weeks after LNG IUD insertion using 16S ribosomal bacterial genes; they found no clinically relevant microbiome change in vaginal fluid after LNG IUD insertion. Another study analyzed the vaginal microbiome changes with different birth control methods, including LNG IUD, and found that LNG IUD users were more often colonized with BV‐associated bacteria than were oral contraceptive users …”
Section: Microbiome and Ec Risk And Protective Factorsmentioning
confidence: 99%